Percutaneous Catheter Drainage in Infected Pancreatitis Necrosis: a Systematic Review - Ke, Lichi (Indian J Surg, 2016)
The primary aim of this study was to present the outcomes of percutaneous catheter drainage (PCD) in patients with infected pancreatitis necrosis. A second aim was to focus on disease severity, catheter size, and additional surgical intervention. A literature search of the PubMed/MEDLINE/Cochrane Library (January 1998 to February 2015) databases was conducted. All randomized, non-randomized, and retrospective studies with data on PCD techniques and outcomes in patients with infected pancreatitis necrosis were included. Studies that reported data on PCD along with other interventions without the possibility to discriminate results specific to PCD were excluded. The main outcomes were mortality, major complications, and definitive successful treatment with percutaneous catheter drainage alone. Fifteen studies of 577 patients were included. There was only one randomized, controlled trial, and most others were retrospective case series. Organ failure before PCD occurred in 55.3 % of patients. With PCD alone, definitive successful treatment was 56.2 % of patients. Additional surgical intervention was required after PCD in 38.5 % of patients. The overall mortality rate was 18 % (104 of 577 patients). Complications occurred in 25.1 % of patients, and fistula was the most common complication. PCD is an efficient tool for treatment in the majority of patients with infected pancreatitis necrosis as the only intervention. Multiple organ failures before PCD are negative parameters for the outcome of the disease. Large catheters fail to prove to be more effective for draining necrotic tissue. However, in the extent of multi-morbid patients, to determine one single prognostic factor seems to be difficult.